Penatalaksanaan Fisioterapi Pada Low Back Pain Miogenik Di RST DR. Soedjono Magelang - Susanto, Herry; , Yulisna Mutia Sari, SST.FT, M.Sc (GRS) (2015)
Background: Low Back Pain is pain that is felt in the lower back region, can be a local pain, and radicular pain or both. Pain originating from the lower back can berujuk other regions or otherwise derived from other areas in the felt in the lower back area, then do a treatment of physiotherapy by using modalities of physiotherapy in the form Transcutaneus Electrical Nerve Stimulation (TENS), Short Wave Diathermy (SWD), and William's Fleksion therapy. Objective: To investigate the implementation of physiotherapy in reducing pain, increasing range of motion (LGS), and reduction of muscle spasm in conditions of Low Back Pain. Therapy: modalities used in the case of Low Back Pain is Transcutaneus Electrical Nerve Stimulation (TENS), Short Wave Diathermy (SWD), and William's Fleksion Exercise Therapy. Results: The results obtained after the conducted therapy 6 times with modalities SWD, TENS, and Therapeutic Exercise William's Fleksion are as follows: pain silent T1 = 0 mm to T6 = 0 mm, tenderness T1 = 60 mm to T6 = 30 mm , pain motion T1 = 20 mm to T6 = 0 mm, LGS Trunk Flexion T1 = 6 cm into T6 = 7 cm, LGS extension Trunk T1 = 2 cm into T6 = 2 cm. Conclusion: SWD, TENS, and William's Fleksion Exercise therapy can reduce motion tenderness and pain, improve LGS, and reducing muscle spasm in conditions of Low Back Pain.